Inequality and Charity. (August 2017) - Mastromatteo, Giuseppe; Russo, Francesco Flaviano
Highlights: We analyze individual-level data on the participation in charitable organizations. We regress charity participation on inequality. We find that inequality is positively associated with charity participation. Gender, religiosity, and education also explain charity participation. There is no evidence that welfare expenditures crowd out charity participation. Summary: We study empirically the relationship between inequality and active charity participation. Increased inequality can trigger feelings of empathy and compassion, thereby increasing altruism, and it can enhance the worm-glow feeling associated with giving. However inequality can also increase social distance and, therefore, social segregation, decreasing the participation to charities because of a weaker identification with the needy. Our empirical analysis features individual data on charity participation from the World Values Survey, merged with country-level information on inequality from the World Bank Development Indicators. We find that income inequality is positively associated with the probability to actively participate in charitable organizations, even after controlling for economic, sociological, demographics, cultural, and religious factors. We also find that women, religious people, and more educated individuals have a higher probability to actively participate in charities. Since charitable organizations mostly perform redistributive tasks, we also checked whether the generosity of the welfare state crowds out the participation in them, but we found no evidence of this relationship.